Tickling the heart: integrating social emotional learning into medical education to cultivate empathetic, resilient, and holistically developed physicians - Hsu, Wei-Chin; Fuh, Lih-Jyh; Liao, Shih-Chieh (Frontiers in Medicine, 2024)
Objectives Advancements in technology have improved healthcare quality but shifted the focus to efficiency, negatively impacting patient– doctor relationships. This study proposes integrating social–emotional learning (SEL) into medical education to address this issue. Key Arguments SEL is based on social learning theory and has a focus on emotion management, stress management, empathy, and social skills. Through SEL, students can develop social and emotional skills by observing, interacting with, and imitating others. Incorporating SEL into medical education would ensure that physicians develop the social and emotional skills necessary to form positive relationships with patients and to cope with the emotional demands of medical work. SEL comprises six domains, namely, the cognitive, emotion, social, values, perspective, and identity domains. These six domains are closely related to the six core competencies the Accreditation Council for Graduate Medical Education (ACGME) indicated every doctor should possess, which indicates that the domains of SEL are highly relevant within the context of medical education. Furthermore, SEL can lead to the development of empathy, which can improve physicians’ ability to understand patients’ perspectives and emotions, and resilience, which can enable physicians to more effectively cope with the demands of their work, and it can lead to holistic development, with doctors gaining an understanding of both the technical and humanistic aspects of their work. Conclusion Incorporating SEL in medical education would enable doctors to develop key social and emotional skills that would improve their ability to provide holistic medical services and therefore would improve overall medical systems.